VACCINIUM UTTERIDGEI (ERICACEAE), A NEW SPECIES (SECT. BRACTEATA) FROM INDONESIAN NEW GUINEA - Argent, G. (Edinburgh Journal of Botany, 2014)
A new species of Vaccinium section Bracteata (Ericaceae), Vaccinium utteridgei Argent, presently only known from the type locality in Papua (West New Guinea), Indonesia, is described. Its distinctive characters are discussed and comments made on the differences between this and related species.